2022
DOI: 10.3389/fnins.2022.1017953
|View full text |Cite
|
Sign up to set email alerts
|

Placental transcriptional signatures associated with cerebral white matter damage in the neonate

Abstract: Cerebral white matter is the most common anatomic location of neonatal brain injury in preterm newborns. Factors that predispose preterm newborns to white matter damage are understudied. In relation to studies of the placenta-brain-axis, dysregulated placental gene expression may play a role in preterm brain damage given its implication in programming early life origins of disease, including neurological disorders. There is a critical need to investigate the relationships between the placental transcriptome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Further, impaired UPF2 function has been associated with neurodevelopmental dysfunction by activating the immune response (Johnson et al, 2019). Highlighting the potential relationship of the altered expression of these genes in the placenta and brain damage in the ELGAN neonate, four of the ASD predictors were also associated with cerebral white matter damage in neonates, namely, BAZ2A , MT‐CO3 , Bromodomain Containing 7 ( BRD7) and Phosphoglucomutase 5 Pseudogene 2 ( PGM5P2 ) (Marable et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, impaired UPF2 function has been associated with neurodevelopmental dysfunction by activating the immune response (Johnson et al, 2019). Highlighting the potential relationship of the altered expression of these genes in the placenta and brain damage in the ELGAN neonate, four of the ASD predictors were also associated with cerebral white matter damage in neonates, namely, BAZ2A , MT‐CO3 , Bromodomain Containing 7 ( BRD7) and Phosphoglucomutase 5 Pseudogene 2 ( PGM5P2 ) (Marable et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal placental function during pregnancy is tied to adverse later‐life outcomes in the offspring including heart disease, obesity, and impaired neurodevelopment (Barker et al, 1990; Bronson & Bale, 2016). In particular, alterations in the placental transcriptome have been linked to brain damage and to the development of adverse neurodevelopmental outcomes (Bangma et al, 2021; Freedman et al, 2022; Marable et al, 2022; Oldenburg et al, 2021) supporting the placenta‐brain‐axis. Still, the role of the placental epigenome in regulating these transcriptome‐level changes is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth [78,79] and cerebrovascular disease [80,81] are associated with systemic inflammation. In the ELGAN cohort, neonatal systemic inflammation was associated with increased risks of cerebral palsy, learning and development deficiencies, and reduced white and grey matter volumes in the brain [82][83][84][85]. Fetuses with biomarkers of placental inflammation were more likely to exhibit neonatal systemic inflammation.…”
Section: Prematurity or Lbw And Brain Disordersmentioning
confidence: 97%
“…Interestingly, Igf1 was one of the ligands which appeared to be dysregulated by PAE in the present placenta-cortex signature. In relation to neuroplacentology, a recent clinical study aimed to establish a transcriptomic placental signature of neonates who developed cerebral white matter damage [44]. The results showed that in the group of infants with white matter lesions, several processes such as inflammation were dysregulated in the placenta [44].…”
Section: Placenta Dysfunction and Brain Development A Growing Concept...mentioning
confidence: 99%
“…In relation to neuroplacentology, a recent clinical study aimed to establish a transcriptomic placental signature of neonates who developed cerebral white matter damage [44]. The results showed that in the group of infants with white matter lesions, several processes such as inflammation were dysregulated in the placenta [44]. However, due to the difficulty of obtaining brain tissues from human neonates, such clinical studies fail to demonstrate functional/mechanistic links.…”
Section: Placenta Dysfunction and Brain Development A Growing Concept...mentioning
confidence: 99%